Loteng (Selodor Bhanteng): Media Nostalgia dalam Menanamkan Konsep Matematika pada Anak Madura - Dhofir Dhofir; Durroh Halim; Sayyidatun Nisa; Moh. Zayyadi (Jurnal Elemen, 2019)
This research aims to explore the mathematical concepts through games on traditional loteng played the son of Madura. The type of data in this study was qualitative research with an ethnographic approach. An ethnographic approach is an approach that is carried out empirically and theoretically to generate an image of deeper analysis and about the culture in the society, in this case, is the traditional game of the loteng. Ethnography approach is a greater emphasis on cultural findings that occurs in a community. The results of this research are in the loteng; there is the concept of a flat wake, addition, subtraction, multiplication, division, even and odd numbers. In addition, loft game can be as nostalgic in a media embed mathematical concepts in the game.